2023
DOI: 10.1002/ajmg.a.63192
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measures of motor development in Angelman syndrome

Abstract: Angelman Syndrome is a rare neurodevelopmental disorder characterized by developmental delay, lack of speech, seizures, intellectual disability, characteristic behavior, and movement disorders. Clinical gait analysis provides the opportunity for movement quantification to investigate an observed maladaptive change in gait pattern and offers an objective outcome of change. Pressure‐sensor‐based technology, inertial and activity monitoring, and instrumented gait analysis (IGA) were employed to define motor abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Digital outcome measures attracted attention in the neuromuscular diseases field, with one outcome from a wearable device, SV95C, recently approved by the EMA as an outcome measure in clinical trials for Duchenne’s Muscular Dystrophy [ 14 , 15 ]. A recent study using pressure-sensor-based technology, inertial and activity monitoring, and instrumented gait analysis (IGA) in children with AS demonstrated that wearable technologies could identify differences in gait compared to neurotypical children, and could capture gait decline in children with AS over the course of the disease [ 24 ]. This suggests that wearable measures of gait could provide an objective outcome measure for this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Digital outcome measures attracted attention in the neuromuscular diseases field, with one outcome from a wearable device, SV95C, recently approved by the EMA as an outcome measure in clinical trials for Duchenne’s Muscular Dystrophy [ 14 , 15 ]. A recent study using pressure-sensor-based technology, inertial and activity monitoring, and instrumented gait analysis (IGA) in children with AS demonstrated that wearable technologies could identify differences in gait compared to neurotypical children, and could capture gait decline in children with AS over the course of the disease [ 24 ]. This suggests that wearable measures of gait could provide an objective outcome measure for this disease.…”
Section: Discussionmentioning
confidence: 99%